Rejsekatalog 2000-2009 - Ringgaard, Dan (Passage - Tidsskrift for litteratur og kritik, 2010)
Dan Ringgaard: “Travel Catalogue 2000-2009” Travel in literature has moved beyond the genre of the travelogue. As travel has become an all-pervading part of globalised life it has creolised the entire domain of literature. This article catalogues eleven types of literature where travel plays a dominant part and argues that literary travels have increased and transmuted in Danish literature of the last decade.